POLA KOMUNIKASI MASYARAKAT DESA SUMBERMULYO DALAM MENJAGA KERUKUNAN MASYARAKAT MULTIKULTURAL - Suyitno .; Fawaizul Umam (Indonesian Journal of Islamic Communication, 2020)
Communication is an activity of humans as social creatures who cannot live without others. Meanwhile, communication is the process of conveying and receiving messages. The purpose of communication is to influence the communicant to do what is meant in the message. Communication can be success if people have closeness or similarity in understanding the message of communication. Otherwise, conflict will occur. A conflict will affect to the harmony. Conflict can be strengthen the harmony or divide a nation. To facilitate the communication process, a pattern (form, model) is needed in communication, especially communication between cultures or between religions. Culture and religion are very vulnerable to create a conflict, so communication between cultures or religions in Indonesia is very needed, since Indonesian is very plural. In other words, the function of communication is to maintain multicultural or multi-religious harmony. The purpose of this study is to determine the communication patterns of the Sumbermulyo community, Pesanggaran sub-district, Banyuwangi regency in maintaining multicultural community harmony. In addition, this study is qualitative. In Determination of informants, it uses snowball techniques, while data are collected by interviews, structured interviews, and documentation. In analysing the data, it starts from data collection, data reduction, data presentation to drawing conclusions. The results of this study shows that the formation of the communication patterns of the Sumbermulyo community is influenced by the great power of Javanese culture. It is able to influence the communication of the Sumbermulyo community to be harmonious.